Enhancing growth and production of carrot plant by spraying aqueous barley sprouts extract, trehalose, and calcium - Al-Khafaji, Aseel M. H. H.; Al-jubouri, Kadhim D. H. (Journal of Kerbala for Agricultural Sciences, 2022)
This research was implemented at vegetable field of the College of Agricultural Engineering Sciences - University of Baghdad during fall seasons, 2018 and 2019. The experiment was conducted using factorial within Randomized Complete Block Design arrangement with three factors and replicates (3X3X2). The aqueous barley sprouts extract (B0, B1) (0, 100 g.L-1) represented the first factor. Trehalose (T0, T1, T2) (0, 50, 75 mmole. L-1) represented the second factor. Calcium (C0, C1, C2) (0, 1, 2 ml.L-1) represented the third factor. The research objectives are assessing the impact of the mentioned factors and their interaction on carrot growth and production. Results showed the superiority of three ways interaction treatment B1T2C1 in producing significant increases nitrogen percent in leaves (2.857, 2.9%), roots (1.273, 1.283%), and carrot production (161.6, 159 ton. ha-1) for both seasons respectively in compare with control treatment B0T0C0.